ANALISIS LOG SISTEM PADA SECURITY INFORMATION AND EVENT MANAGEMENT (SIEM) UNTUK MENDETEKSI SERANGAN BRUTE FORCE - Caleb Sebastian, (2024)
Brute-force attacks are a common type of cyber attack that target SSH and RDP protocols. These attacks can cause significant damage to organizations. One solution for detecting brute-force attacks is to use Security Information and Event Management (SIEM). SIEM can monitor login activity and identify suspicious patterns. This study uses Wazuh, a popular open-source SIEM platform, to detect brute-force attacks targeting SSH and RDP protocols. The results of the study show that Wazuh can detect brute-force attacks effectively. Wazuh can block IP addresses that attempt to log in with the wrong password repeatedly. This study provides valuable information for organizations in their efforts to improve their security against brute-force attacks. Organizations can use SIEM, such as Wazuh, to detect brute-force attacks and provide a timely response.